Financing the EU Neighbourhood – Key Facts and Figures for the Eastern Partnership - Ioana Sandu; Gabriela Dragan (CES Working Papers, 2016)
The EU is permanently trying to secure its proximity by creating a “ring of friends” in the neighbourhood. Thus, stabilization through economic integration and modernization have been the purpose of the European Neighbourhood Policy (the ENP) since its creation, in 2004. Successive reviews of the ENP in the past decade have aimed to customize support to different needs of the partners. Funding has been allocated according to the level of commitment to reform of the EU neighbours. The six small states of the Eastern Partnership (EaP) have benefitted not only from common ENP provisions, but also from specific instruments dedicated to their particular situation. Bilateral and multi-country programmes included in the European Neighbourhood Instrument (ENI), but also instruments from other EU policies and support from the International Financial Institutions (IFI) have helped the EaP members to achieve progress in EU approximation.
Keywords: F55; G23; O19; P33; 330; funding; financial instruments; Eastern neighbourhood; “more for more”; reform